Self-esteem, Social Support, Personality and Psychological Well Being of Junior High School Student - Mufied Fauziah; Dany Moenindyah Handarini; Muslihati Muslihati (Pascasarjana UM, 2018)
Abstract: The aims of this study was to understand how the relationship between self-esteem, social support, extraversion personality, agreeableness personality, conscientiousness personality, neuroticism personality, openness personality, and psychological well-being of the public junior high school students in Malang city. This study was a non-experimental study with correlational design. Results of this research showed a variable that has a relationship with the psychological well-being is self-esteem, social support, personality agreeableness, neuroticism personality and conscientiousness personality. Accumulated seventh influence of independent variables equal to 61% of the variance of psychological well-being can be explained by three independent variables, and the rest as many as 39% are caused by other factors.Key Words: self-esteem, social support, psychological well-being, junior high school studentsAbstrak: Penelitian ini bertujuan untuk mengetahui hubungan antara harga diri, dukungan sosial, kepribadian extraversion, kepribadian agreeableness, kepribadian conscientiousness, kepribadian neuroticism, kepribadian openness dan psychological well-being Siswa SMP Negeri Se-Kota Malang. Pendekatan yang digunakan adalah non-experimental research dengan jenis penelitian korelasional. Hasil penelitian menunjukkan variabel yang memiliki hubungan dengan psychological well-being adalah harga diri, dukungan sosial, kepribadian agreeableness, kepribadian neuroticism dan kepribadian conscientiousness. Akumulasi pengaruh ketujuh variabel independen sebesar 61% varian psychological well-being dapat dijelaskan ketiga variabel bebas, dan sisanya yaitu sebanyak 39 % disebabkan oleh faktor lain.Kata kunci: harga diri, dukungan sosial, kepribadian, psychological well-being, siswa SMP